2015
DOI: 10.1016/j.ajem.2014.12.067
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of interfacility transfer for ED patients with ST-elevation myocardial infarction

Abstract: Objectives Most U.S. hospitals lack primary percutaneous coronary intervention (PCI) capabilities to treat patients with ST-elevation myocardial infarction (STEMI) necessitating transfer to PCI-capable centers. Transferred patients rarely meet the 120-minute benchmark for timely reperfusion and referring EDs are a major source of preventable delays. We sought to use more granular data at transferring EDs to describe the variability in length of stay at referring EDs. Methods We retrospectively analyzed a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“… 3 Further heightening the importance of the role of the ED and its timeliness is that most patients with STEMI initially present to U.S. EDs. 4 Not only are transfers from U.S. EDs increasing in frequency for patients with STEMI, 5 but the time spent at transferring EDs is longer and more variable than either the transportation or pPCI center phases. Considering the role of the emergency care system is to rapidly identify, coordinate and treat time-sensitive emergency conditions like STEMI, the timeliness and performance of the ED for patients with STEMI is central to high-quality care.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Further heightening the importance of the role of the ED and its timeliness is that most patients with STEMI initially present to U.S. EDs. 4 Not only are transfers from U.S. EDs increasing in frequency for patients with STEMI, 5 but the time spent at transferring EDs is longer and more variable than either the transportation or pPCI center phases. Considering the role of the emergency care system is to rapidly identify, coordinate and treat time-sensitive emergency conditions like STEMI, the timeliness and performance of the ED for patients with STEMI is central to high-quality care.…”
Section: Introductionmentioning
confidence: 99%
“…The review of literature shows that uninsured STEMI patients present conflicting data. [7][8][9][10][11] For the most part, uninsured patients are transferred out and discharged more readily from the receiving facilities, possibly due to the potential financial impact. In patients where time critical diagnosis (TCD) is encountered, guidelines dictate transfer to a facility where optimal management is available.…”
Section: Discussionmentioning
confidence: 99%
“…Herrin et al discovered a small but statistically significant delay in door-to-balloon time for Medicaid and uninsured STEMI patients versus the privately insured, [7] while Ward et al from found that uninsured STEMI patients are more likely to be transferred but it is unclear if this is based on non-availability of PCI or purely due to lack of insurance. [8] In our study, we sought to determine the impact of insurance status on inter-facility transfer times and length of stay for STEMI patients.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Second, the list of system practices may be incomplete. Third, additional factors not captured in our survey - such as collaborative relationships between EMS agencies, STEMI referral hospitals, and STEMI receiving centers 13,14 and decision-making processes at the STEMI referral hospital 15 – may influence DIDO and first-DTB times. Finally, our sample size may have been insufficient to detect a more subtle relationship between system practices and DIDO and FIRST-DTB times.…”
Section: Discussionmentioning
confidence: 99%